Case Report: Refractory Mycoplasma pneumoniae pneumonia complicated by pulmonary embolism and infarction in a child - Zhang, Jianqin; Zhang, Zhe; Zhu, Ziwei; Cheng, Li; Shan, Yuxia (Frontiers in Pediatrics, 2025)
Mycoplasma pneumoniae (MP) is a significant pathogen of community-acquired pneumonia in children, typically following a benign course. However, some cases may progress to severe or refractory MP pneumonia (SMPP or RMPP) and lead to thromboembolic complications. This report describes a rare case of a 9-year-old boy with RMPP complicated by bilateral pulmonary embolism (PE) and pulmonary infarction. The patient initially presented with a fever and cough. Despite 24 days of prior treatment at another hospital, including macrolide, carbapenem, and tetracycline antibiotics and corticosteroids, he remained febrile with persistent wheezing when transferred to our institution. Through some laboratory findings and contrast-enhanced chest computed tomography, he fulfilled the diagnostic criteria for both SMPP and RMPP, accompanied by a PE with pulmonary infarction. A multidisciplinary therapeutic approach combining anti-infective agents (linezolid and moxifloxacin), anti-inflammatory therapy (methylprednisolone), and adjusted anticoagulation (low-molecular-weight heparin followed by rivaroxaban) led to rapid clinical improvement and normalization of inflammatory/coagulation markers. Complete resolution of the PE was further demonstrated by 3-month follow-up imaging. Residual focal necrosis in the right lower lobe was observed. This case highlights the potential for severe thromboembolic events in pediatric RMPP and underscores the importance of early recognition of imaging features (e.g., vascular filling defects and wedge-shaped infarcts) and integrated multidisciplinary management to optimize patient outcomes.